Infinite servers queue systems computational simulation - Ferreira, M. A. M.; Andrade, M. (Proceedings of 12th Conference on Applied Mathematics, APLIMAT 2013, 2013)
For many parameters of interest in the study or application of queuing systems either there are not theoretical results or, existing, they are very complicated what makes their utility doubtful. In this situation it is very common to use simulation methods in order to get useful results. Here a Fortran program to simulate infinite servers queuing systems is presented. Through it, some experiences are performed and the respective results are used to conjecture about some interesting quantities of those systems, mainly about the busy period.